2017
DOI: 10.1016/j.jped.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal outcomes according to different therapies for gestational diabetes mellitus

Abstract: The pediatrician in the delivery room can expect different outcomes for diabetic mothers based on the treatment received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
3
15

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 22 publications
3
25
3
15
Order By: Relevance
“…However, a study conducted in Fortaleza, Brazil, on which professionals provided information about the disease during prenatal care found that 58.8% of the respondents answered that they had received no information about the disease. Only 17.6% stated that they had received the information from nurses; 17.6% from physician; and 6.0% from pharmacy professionals (6) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a study conducted in Fortaleza, Brazil, on which professionals provided information about the disease during prenatal care found that 58.8% of the respondents answered that they had received no information about the disease. Only 17.6% stated that they had received the information from nurses; 17.6% from physician; and 6.0% from pharmacy professionals (6) .…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus increases the rate of fetal malformations and alters the growth of the unborn child. The incidence of congenital malformations varies from 5.0 to 10.0%, two to three-fold higher than that observed in the general population, and also accounting for about 40.0% of perinatal deaths (6) . Although there is a notable scientific interest in establishing the precise triggering etiologic factors of this clinical condition, few researchers have quantified the risks of major neonatal complications in pregnant women diagnosed with this disease (7) .…”
Section: Introductionmentioning
confidence: 85%
“…Watanabe et al 31 also found a higher rate of cesarean sections among women treated with insulin; in addition, 40% (n ¼ 4) of them were overweight, and 10% (n ¼ 1) had a BMI 30 kg/m 2 before pregnancy, which was not significant. 31,32 Regarding the maternal age and insulin use, no significant differences were found either. Differently, a retrospective study 32 (n ¼ 612 GD cases) showed that the mean age of the women who used insulin was 31.4 years versus 30.9 years for those who did not use it.…”
Section: Discussionmentioning
confidence: 80%
“…variations were found in the indication of MH in the studies analyzed, where in two of them,Oliveira et al (2019) andSilva et al (2019), there is a percentage greater than 40% in the indication of the drug, while in the other study of the same year byRodrigues et al (2019) we have a decrease in indication, below 30%. It was also observed that in the studies byAmaral et al (2015),Silva et al (2016) andSilveira-Filho et al (2018) the indication of the MH was in a range above 30%.…”
mentioning
confidence: 73%